ARSENIC REMOVAL FROM THE WATER OF THE LOCUMBA RIVER (ITE DISTRICT, TACNA REGION-PERU), USING FERRIC CHLORIDE - Machaca Rodríguez, Angélica (2022)
The objective of the present investigation was to propose an alternative solution to the problem of lack of hours of underground water supply for human consumption in the district of Ite, carrying out the treatment with ferric chloride for the removal of arsenic (0,4930 ± 0,0642 mgL-1) of natural origin from the Locumba river; which will be used as an additional source of water. Methodology: a jug testing equipment was used to study the operating conditions. A fractional factorial analysis was applied and then a response surface analysis to study the operating variables: their influence, linearity and the appropriate operating conditions.Additionally, speciation and analysis of arsenic (As+3) were performed using solid phase extraction (SFS) and voltammetry. Results: It was possible to reduce the number of operation variables from five to three variables (FeCl3 dose, flocculation speed, sedimentation time); The response surface design was applied to the latter, determining that the samples that were filtered after the treatment process; in all operating conditions they showed arsenic concentrations lower than 0,01 mgL-1. In the unfiltered samples, concentrations below 0,01mgL-1 were achieved in two operating conditions. The results of the unfiltered arsenic samples were fitted to a quadratic model, obtaining an r2-adjusted value of 94%. The found quadratic model was shown to be a saddle point. The best operating conditions for the greatest removal of arsenic (0,00924 mgL-1) in the unfiltered samples were: 40 mgL-1 of FeCl3 dose, 60 rpm as flocculation speed, 80 minutes of sedimentation time, pH =7 and a flocculation time of 25 minutes. Conclusions: It is possible to remove arsenic from Locumba river water to levels suitable for human consumption using ferric chloride as coagulant under the operating conditions found in this study. It should be kept in mind that pH is one of the most importantvariables in this type of treatment process and the use of sulfuric acid to regulate it is one of the best alternatives due to the cost and proximity of Ite to the Southern Copper Corporation mining company, which produces this chemical input.